The effect of Animal-assisted therapy on prosocial behavior and emotional regulation in autistic children with varying verbal abilities: A pilot study. - Michele Kilmer; Minju Hong; Victor Akakpo; Terria Hawley; Danielle Randolph; Sarah Huetter; Allison Reichel; Madelyn Bowden (PLoS ONE)
Background The use of animal-assisted therapy (AAT) has increased in the pediatric autism population. However, studies detailing differences in human-animal interaction between autistic children and animals along with the longevity of reported outcomes associated with AAT need further exploration. The purpose of this pilot study was to evaluate these factors. Methods A quantitative research design with convenience sampling was used to categorize pediatric participants into two groups (nonverbal or verbal) based on their verbality. Two human-animal ethogram and two questionnaires were utilized to assess behavior during and apart from AAT sessions. A total of 2,281 interactions and behaviors occurring during AAT sessions were examined. Results Both groups interacted well with the canine. The verbal group interacted mostly with commands while the nonverbal group showed more affectionate behaviors. Conclusion Mental health practitioners can use canines to enhance therapeutic outcomes in autistic children regardless of the child's verbality.